1998
DOI: 10.1111/j.1467-8624.1998.tb06163.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Study of Attachment Disorganization/Disorientation

Abstract: The research explores the antecedents and consequences of attachment disorganization from a prospective longitudinal perspective. The relations of attachment disorganization I disorientation to endogenous (e.g., maternal medical history, infant temperament) and environmental (e.g., maternal caregiving quality, infant history of abuse) antecedents and to behavioral consequences from 24 months to 19 years are examined. For the 157 participants in the longitudinal study, attachment disorganization was correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
306
2
29

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(350 citation statements)
references
References 48 publications
13
306
2
29
Order By: Relevance
“…Also, certain types of traumatic stressors commonly encountered in such DD groups are not tapped by standard childhood maltreatment scales, such as sudden death of family and close friends, growing up with severely mentally ill parents, or experiencing a severe traumatic episode of mental illness that triggers chronic depersonalization . In addition to maltreatment, prospective studies have found that serious disruptions of the early mother-infant dyad contribute to increased dissociation scores in late adolescence and adulthood (Hesse and Main 2006, Lyons-Ruth et al 2006, Ogawa et al 1997, Carlson 1998. Genetic contributions to dissociation have also been reported by some researchers (Becker-Blease et al 2004, Jang et al 1998).…”
Section: Discussionmentioning
confidence: 93%
“…Also, certain types of traumatic stressors commonly encountered in such DD groups are not tapped by standard childhood maltreatment scales, such as sudden death of family and close friends, growing up with severely mentally ill parents, or experiencing a severe traumatic episode of mental illness that triggers chronic depersonalization . In addition to maltreatment, prospective studies have found that serious disruptions of the early mother-infant dyad contribute to increased dissociation scores in late adolescence and adulthood (Hesse and Main 2006, Lyons-Ruth et al 2006, Ogawa et al 1997, Carlson 1998. Genetic contributions to dissociation have also been reported by some researchers (Becker-Blease et al 2004, Jang et al 1998).…”
Section: Discussionmentioning
confidence: 93%
“…Secure infants also have improved emotional regulation, express more positive emotion and exhibit appropriate persistence and flexibility in response to stress. Infant disorganized attachment has been associated with the highest risk of developing later psychopathology [88], including dissociative disorders [89], aggressive behavior [90], conduct disorder and self-abuse [15]. Thus, aspects of the mother-infant interaction which have been demonstrated to be transmitted intergenerationally in humans and primates have profound effects on infant development and thus can mediate the inheritance by offspring of increased risk or resilience to physical or emotional disorder.…”
Section: Implications Of the Transgenerational Effects Maternal Carementioning
confidence: 99%
“…Moreover, highly imaginative children's narratives might have been more rich and elaborated than those of other children, contributing to higher scores on the stem measure of dissociation. In one of the most comprehensive longitudinal studies (Carlson, 1998), the teacher rating scale used to assess dissociation consisted of five items ("explosive and unpredictable behavior," "strange behavior," "gets hurt a lot, accident-prone," "confused or seems to be in a fog," and "stares blankly") that may not be specific to dissociation. Moreover, the link between a measure of early caregiving and the DES in adolescence was a modest r ϭ .21.…”
Section: Commentmentioning
confidence: 99%